2013
DOI: 10.4161/chan.23968
|View full text |Cite
|
Sign up to set email alerts
|

Two serine residues on GluN2A C-terminal tails control NMDA receptor current decay times

Abstract: NMDA receptors are glutamate-activated, Ca ( 2+) -permeable ion channels with critical roles in synaptic transmission and plasticity. The shape and size of their current is modulated by several kinase/phosphatase systems, and numerous residues located on the receptors' intracellular C-termini are phosphorylated in vivo. To investigate the mechanisms by which phosphorylation may control channel gating, we examined the single-channel behaviors of receptors carrying the S900A or S929A substitution in their GluN2A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…In contrast however, PKA phosphorylation of N1/N2A receptors lengthens NMDA receptor-mediated EPSCs in neurons (44), and the Ser/Ala modification of known targets on N2A CTD (Ser-900 or Ser-929) alters receptor gating in a manner similar to that described here for N1/N2B S1166A and PKI treatment of wild-type N1/N2B (45). Together, these results suggest that the phosphorylation status of N2A-containing receptors was not altered by PKI treatment.…”
Section: Discussionsupporting
confidence: 61%
“…In contrast however, PKA phosphorylation of N1/N2A receptors lengthens NMDA receptor-mediated EPSCs in neurons (44), and the Ser/Ala modification of known targets on N2A CTD (Ser-900 or Ser-929) alters receptor gating in a manner similar to that described here for N1/N2B S1166A and PKI treatment of wild-type N1/N2B (45). Together, these results suggest that the phosphorylation status of N2A-containing receptors was not altered by PKI treatment.…”
Section: Discussionsupporting
confidence: 61%
“…However, we found that LTD was not associated with a change in decay kinetics of EPSC NMDA , suggesting no change in NMDAR subunit composition in our experiments. PKA activity has been shown to enhance NMDAR function via phosphorylation of NR1, NR2A, and NR2B subunits (44)(45)(46); thus, a reduction in PKA activity and subsequent dephosphorylation of NMDARs may provide a potential mechanism underlying the decrease in NMDAR currents (44).…”
Section: Discussionmentioning
confidence: 99%
“…2; Leonard and Hell 1997;Tingley et al 1997;Murphy et al 2014). For example, PKA phosphorylation of two sites in the cytoplasmic C-terminal tail of GluN2A subunits (serine 900 and 929) and at serine 1166 in the C-terminus of GluN2B subunits increases channel open probability (Krupp et al 2002;Maki et al 2013;Aman et al 2014). In addition to effects on channel gating, PKA activation also enhances the Ca 2+ permeability of NMDAR ion channels (Skeberdis et al 2006), an effect mediated by phosphorylation of GluN1 subunits at serine 897 and GluN2B subunits at serine 1166 Murphy et al 2014).…”
Section: Molecular Mechanisms Underlying the Enhancement Of Ltp By B-mentioning
confidence: 99%